THE INFLUENCE OF INNOVATIVE LEARNING MODELS AND PEDAGOGICAL COMPETENCE ON TEACHER PERFORMANCE AND ITS IMPLICATIONS FOR THE QUALITY OF EDUCATION IN PUBLIC ELEMENTARY SCHOOLS IN SERANG REGENCY - Deviana, Sinta; Suparmoko, Muhammad; Wiguna, Wahyu (Yayasan Education and Social Center, 2025)
Teacher performance in learning is the performance carried out by a teacher in carrying out his duties and responsibilities in providing learning guidance in the form of knowledge and skills so that there is an increase in student learning achievement.The purpose of this study was to analyze the direct and indirect effects of innovative learning models and pedagogical competence on teacher performance and educational quality. This study was conducted in elementary schools in Serang Regency with a sample population of 189 students, drawn using random sampling. This study used path analysis and the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of this study indicate that hypothesis testing shows that the innovative learning model has a positive and significant influence on teacher performance (β=0.497 t=6.417 p=0.000). The innovative learning model has a positive and significant influence on the quality of education. (β=0.205 t=2.499 p=0.012). pedagogical competence has a positive and significant influence on teacher performance (β=0.299 t=4.127 p=0.000). pedagogical competence has a positive and significant influence onquality of education (β=0.262 t=3.945 p=0.000. teacher performance has a positive and significant influence onquality of education (β=0.425 t=4.561 p=0.000). Innovative learning modelspositive influence on teacher performance throughquality of education (β=0.133 t=3.073p=0.002). pedagogical competence has a positive influence on teacher performance throughquality of education (β=0.171 t=2.958 p=0.003).So it can be concluded that there is a significant influence between innovative learning models and pedagogical competence on teacher performance with the quality of education as mediation in elementary schools in Serang Regency.